2000
DOI: 10.1007/s002230010039
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alteration in Bone Mineral Density and Biochemical Markers for Bone Metabolism in Nephrotic Patients Receiving High-Dose Glucocorticoid and One-Cycle Etidronate Therapy

Abstract: It is widely known that glucocorticoids induce and accelerate osteoporosis. High-dose glucocorticoids are administrated daily to patients in the acute phase of nephrotic syndrome. It could be inferred that high-dose glucocorticoids rapidly decrease patients' basal bone mineral density (BMD) and this accelerates the natural progress of osteoporosis associated with aging or menopause. Nine nephrotic patients (male/female: 5/4) without previous prednisolone administration were chosen to measure BMD and the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…After a median of 18 days following GC initiation, every 1 mg/m 2 increase in GC therapy (prednisone equivalents) was associated with a decrease in spine BMD Z-score of almost 0.4 standard deviation (SD). This finding was consistent with a recent report in adult GC-treated NS in which significant declines in spine BMD Z-scores were evident after just 12 weeks of GC therapy [10]. Similarly, a large cross-sectional case-control study showed lower spine bone mineral content after 4 years of GC exposure in children with steroid-sensitive NS, suggesting the potential for residual bone mass deficits in the longer term [11].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…After a median of 18 days following GC initiation, every 1 mg/m 2 increase in GC therapy (prednisone equivalents) was associated with a decrease in spine BMD Z-score of almost 0.4 standard deviation (SD). This finding was consistent with a recent report in adult GC-treated NS in which significant declines in spine BMD Z-scores were evident after just 12 weeks of GC therapy [10]. Similarly, a large cross-sectional case-control study showed lower spine bone mineral content after 4 years of GC exposure in children with steroid-sensitive NS, suggesting the potential for residual bone mass deficits in the longer term [11].…”
Section: Introductionsupporting
confidence: 92%
“…A number of studies have shown a significant decrease in LS BMD Z-scores in the first few weeks of GC therapy, both in children [36] and in adults [10] with NS. These observations are attributable to the acute effects of GC on bone, as demonstrated in animal models [37], and on trans-iliac bone specimens from adults [38].…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well-known that GCs have a predilection for interference with trabecular bone architecture, both in humans [6] and in animal models [5]. Furthermore, bone resorption markers increase acutely in adults with NS following administration of GCs [28], and are associated with a significant decline in spine BMD after a few weeks of therapy in both adults [28] and children with NS [9]. In addition, spine BMD has been shown to decline rapidly in adults following GC initiation for organ transplantation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the bone loss from the spine of first-time user followed in longitudinal studies [9,20,25,33,38,42,51,56,67,71]. One limitation of evaluating bone loss longitudinally is that daily dose may vary and reduce over time.…”
Section: Onset Of Skeletal Effectsmentioning
confidence: 99%